LUMINANCE AND CHROMATIC DETECTION MECHANISMS OF THE HUMAN VISUAL SYSTEM - Hernández Lloreda, María J. (Anales de Psicología / Annals of Psychology, 2001)
The main goal of this paper is to provide a critical assessment about luminance and chromatic processing by the Human Visual System. Although early experiments seemed to favor a modular architecture (so that each type of information is processed independently) more recent research discover a more complex panorama. Luminance and chromatic contrast interact, both at a physiological and a psychophysical level, with clear asymmetries in the way they contribute to the processing of visual information.